Pengaruh Kepercayaan Merek dan Keterlibatan Konsumen Terhadap Loyalitas Merek Pada Produk Ms Glow - Silfina Saputri M; Andry Stepahnie Titing; Hanif Kurniadi (Global Leadership Organizational Research in Management, 2023)
This study aims to determine: (1) The effect of brand trust on brand loyalty (a study on FISIP USN Kolaka students). (2) The effect of consumer involvement on brand loyalty (a study on FISIP USN Kolaka students). This study uses an approach with quantitative methods. Collecting data in this study using observation, documentation and questionnaires. The population of this study were FISIP students at the Nineteen November University of Kolaka. While the sample of this study amounted to 91 respondents by determining the sample using probability sampling technique. Testing research instruments using validity and reliability tests with SPSS 25. The data analysis technique used in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model tests (outer model) and structural model testing (inner model). ) with Smart PLS 3.0. Based on the research results, it is known that the variable Brand Trust has a positive and significant effect on Brand Loyalty as indicated by the P-Values of 0.000. As well as the variable Consumer Involvement also has a positive and significant effect on Brand Loyalty as indicated by the P-Values of 0.003.